Prevalence and Risk Factors for Diabetic Retinopathy - A Study of 217 Patients from University of Malaya Medical Centre - Tajunisah, I.; Nabilah, H.; Reddy, S.C. (Malaysian Medical Association, 2006)
Two hundred and seventeen diabetic patients attending the eye clinic were examined to determine the prevalence of retinal changes, and the association between diabetic retinopathy and risk factors. A detailed fundus examination was done, after dilating the pupils, using 90 D lens and slitlamp biomicroscope. Diabetic retinopathy was detected in 112 patients (51.6%). Background retinopathy was seen in 40 out of 217 (18.4%), pre-proliferative retinopathy in 11 (5.1%), proliferative retinopathy in 61 (28.1%) and maculopathy in 58 (26.7%) patients. Factors significantly associated with occurrence of retinopathy were duration of diabetes, presence of hypertension and presence of systemic complications (diabetic foot ulcer, lower limb amputation, nephropathy and peripheral neuropathy).